Perilaku Berisiko Terhadap Remaja Akibat Broken Home Di Kecamatan Sangatta Selatan Kota Sangatta - Amanda, Ainun Alfrida (Jurnal Ayurveda Medistra, 2024)
Children who experience a Broken Home due to divorce can experience various kinds of negative things in children such as mental stress, poor child behavior, uncontrollable emotions, and preferring to be alone. Prefer to be alone. This research was qualitative research with a case study research design that used the snowball sampling method with data collection techniques, namely in-depth interviews, observation, and documentation. The instruments in this research were in-depth interview guidelines, field notes, and recording devices like cell phones. Data is processed manually using a matrix sheet using the content analysis method. Results were 11 informants was informants engage in risk behaviors such as smoking, consuming alcoholic beverages, drug abuse, and free sex. Informants who came from broken home families tend to be more able to commit risk behaviors such as smoking, alcohol consumption, drug abuse, and promiscuous sex. Risk behaviors such as smoking, alcohol consumption, drug abuse, and promiscuous sex because they felt that with broken home drugs, and promiscuous sex because they felt that a broken home can make them freer, less vulnerable, and less vulnerable. Being a broken home victim, less affectionate, depressed, and felt sad and supported by a bad friendship environment so that they were more able to carry out these risky behaviors. So that they were more able to carry out these risk behaviors and conclusions Risk behaviors committed by adolescents such as smoking, consuming alcoholic beverages, drug abuse, and promiscuous sex are true. alcohol, drug abuse, and promiscuous sex are indeed a result of broken homes and bad friendships. the result of a broken home and a bad friendship environment. The results of this study are expected that the South Sangatta Sub-district of Sangatta City can work together with the Sangatta City Health Office to conduct educational activities about the science that discusses risky behavior in order to prevent risky behavior. Keywords: Risk behavior, broken home, case study.